Optimizing Teaching and Learning Activities in Fiqh Subjects During the Covid-19 Pandemic - Ani Maftukha; Akhmad Mujani; Abdul Aziz Romdhoni (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This research aims to describe a case regarding the optimization of teaching and learning activities in Fiqh subjects during the Covid-19 pandemic. because this research is motivated by the emergence of the Covid-19 pandemic which currently requires teaching and learning activities to be carried out using Distance Learning (PJJ) or online. This research uses a qualitative approach with a descriptive type. Apart from that, this research will describe a phenomenon of teaching and learning activities that occurred during Covid-19. The research results show that productivity in learning fiqh is also one of the things that must be given as much as possible. For a Muslim, fiqh is the procedures for worship in daily life such as prayer, infaq and alms. In this research, the method used is descriptive qualitative observation. The research results obtained are that there are several ways that educators and students can provide optimal learning activities for fiqh subjects. The way educators do this is by giving assignments, discussions, questions and answers as well as motivating students to participate in fiqh learning with enthusiasm. Meanwhile, the way for students is to divide their time between studying and relaxing, as well as carrying out assignments given by the teacher to be done by reading notebooks.